We want you! Recruitment strategies for the success of a citizen science project on urban wildlife ecology - Schumann, Anke; Greving, Hannah; Bruckermann, Till; Kimmerle, Joachim; Harms, Ute; Brandt, Miriam (Frontiers in Environmental Science, 2024)
In this case study, we report on the recruitment of participants for a citizen science (CS) project on urban wildlife monitoring (about 860 participants), and the consequences of recruitment strategies for achieving the project goals. We describe the approach that we used to identify our target audience and to design the core message for the recruitment campaign. We searched for participants who were interested in wildlife and in the scientific research process. We based the recruitment campaign on the appeal of discovering wildlife in people's immediate surroundings. Recruitment was successful in terms of the number of applications we received. Participants' interests reflected their focus on wildlife, and we discuss how this was reflected in their engagement. We use this case study to highlight the importance of deliberately designing recruitment strategies for CS projects. Such strategies will have implications for participants' motivation and ultimately may influence their contributions to the project. citizens to do so is to engage in citizen science (CS) projects. These are projects in which volunteering citizens participate in scientific research projects and collaborate with scientists (Bonney et al., 2009;Heigl et al., 2019). Yet, finding citizens who volunteer in engaging with scientific research projects can be challenging and different recruitment strategies have been suggested (